numbers 3x + 2y = 12
y = x + 1
Substitution Method
Since y is already isolated in the second equation we can use that value, to substitute for y in the first equation.
3x + 2 (x + 1) = 12
3x + 2x + 2 = 12
5x = 12 − 2
5x = 10
x = 2
Substitute the computed value of x to the second equation to determine the value of y.
y = 2 + 1
y = 3
Elimination Method
3x + 2y = 12
x − y = −1
Multiply the second equation by 2 to eliminate
x or you can also multiply the second equation by 3 to eliminate y. However since it is easier to multiply by 2, I will follow the first method.
3x + 2y = 12
2x − 2y = −2
Adding the two equations eliminates the y variable.
5x = 10
x = 2
Substitute the computed value of x to the second equation to determine the value of y.
y = 2 + 1
y = 3
Solution Set:
(2,3)